The Influence of Online Customer Reviews, Online Customer Ratings, Brand Image, and Price Perceptions on the Decision to Purchase Ventela Shoes on Shopee Marketplace - Rizqullah, Naufal Khosyi; Haryanto, Totok; Rahayu, Tri Septin Muji; Kharismasyah, Alfato Yusnar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the effect of online customer reviews, online customer ratings, brand image, and price perceptions on purchasing decisions for Ventela shoes on the Shopee marketplace. The research subjects were the general public, with sampling using purposive sampling method, with a total sample size of 102 people. Data analysis was carried out using multiple linear regression. The results showed that 1) online customer review has a positive and significant influence on purchasing decisions, 2) online customer rating has a significant positive influence on purchasing decisions, 3) brand image has a positive and significant influence on purchasing decisions and 4) price perception has no influence on purchasing decisions.